Direct polymer additive tooling – effect of additive manufactured polymer tools on part material properties for injection moulding. Issue 10 (17th September 2019) - Kampker, Achim; Triebs, Johannes; Kawollek, Sebastian; Ayvaz, Peter; Beyer, Tom
Abstract : Purpose: This study aims to investigate the influence of additive manufactured polymer injection moulds on the mechanical properties of moulded parts. Therefore, polymer moulds are used to inject standard specimens to compare material properties to specimens produced using a conventional aluminium tool. Design/methodology/approach: PolyJet technology is used to three-dimensional (3D)-print a mould insert in Digital ABS and selective laser sintering (SLS) technology is used to 3D-print a mould insert in polyamide (PA) 3200 GF. A conventionally aluminium milled tool serves as reference. Standard specimens are produced to compare resulting mechanical properties, shrinkage behaviour and morphology. Findings: The determined material characteristics of the manufactured prototypes from the additive manufactured tools show differences in terms of mechanical behaviour to those from the aluminium reference tool. The most significant differences are an up to 25 per cent lower tensile elongation and an up to 63 per cent lower elongation at break resulting in an embrittlement of the specimens produced. These differences seem to be mainly due to the different morphological structure caused by the lower thermal conductivity and greater surface roughness of the polymer tools. Research limitations/implications: The determined differences in mechanical behaviour can partly be assigned to differences in surface roughness and morphological structure of the resulting parts. The exact extend of either cause, however, cannot be clearly determined. Originality/value: This study provides a comparison between the part material properties from conventionally milled aluminium tools and polymer inserts manufactured via additive tooling.